2012
DOI: 10.1111/ddi.12010
|View full text |Cite
|
Sign up to set email alerts
|

Use of predictive habitat modelling to assess the distribution and extent of the current protection of ‘listed’ deep‐sea habitats

Abstract: Aim To demonstrate the application of predictive species distribution modelling methods to habitat mapping and assessment of percentage area-based conservation targets.Location The NE Atlantic deep sea (UK and Irish extended continental shelf limits).Methods MaxEnt modelling of three listed habitats (Lophelia pertusa (Linnaeus, 1758) reef (LpReef), Pheronema carpenteri (WyvilleThomson, 1869) aggregations (PcAggs) and Syringammina fragilissima (Brady, 1883) aggregations (SfAggs)), with some pre-selection of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 72 publications
4
125
0
2
Order By: Relevance
“…Scientists and decision-makers involved in conservation and management also grew an interest for marine habitat mapping (e.g., Ross and Howell, 2013;Selgrath et al, 2016): while habitat maps can serve many purposes, statistics show that habitat mapping studies are most often directly or indirectly set in a context of conservation or management (Figure 1), and the meta-analysis showed that 16 review articles were written on the use of marine habitat mapping for conservation and management between 2003 and 2016. The proportion of habitat mapping studies set in a context of conservation or management is higher in the marine environment (about 67%) than in other types of environments (about 58%) (Figure 1).…”
Section: Habitat Mapping and Spatial Sciences For Conservation And Mamentioning
confidence: 99%
“…Scientists and decision-makers involved in conservation and management also grew an interest for marine habitat mapping (e.g., Ross and Howell, 2013;Selgrath et al, 2016): while habitat maps can serve many purposes, statistics show that habitat mapping studies are most often directly or indirectly set in a context of conservation or management (Figure 1), and the meta-analysis showed that 16 review articles were written on the use of marine habitat mapping for conservation and management between 2003 and 2016. The proportion of habitat mapping studies set in a context of conservation or management is higher in the marine environment (about 67%) than in other types of environments (about 58%) (Figure 1).…”
Section: Habitat Mapping and Spatial Sciences For Conservation And Mamentioning
confidence: 99%
“…Although subjective manual mapping is the most common approach for identifying areas of potential coral habitats (Davies et al 2008;Ross and Howell 2013), more objective and automated approaches have been published (Salcedo-Sanz et al 2016). However, the semi-automated mapping approach presented in this study uses a fast and consistent automatic method and allows inclusion of additional data sets that have been developed within a GIS environment.…”
Section: Semi-automated Mapping: Bgs Seabed Mapping Toolboxmentioning
confidence: 99%
“…Habitat suitability modeling is being used increasingly to predict distribution patterns of VME indicator taxa in the deep sea, where data are particularly sparse, and such models are considered useful for marine ecosystem management (Ross and Howell, 2013;Reiss et al, 2014). Habitat suitability models have been produced for numerous deep-sea taxa (see review by Vierod et al, 2014), but the predicted distributions are dependent on how the models are constructed.…”
Section: Introductionmentioning
confidence: 99%